2017
DOI: 10.1104/pp.17.00713
|View full text |Cite
|
Sign up to set email alerts
|

Auxin and ROP GTPase Signaling of Polar Nuclear Migration in Root Epidermal Hair Cells

Abstract: ORCID IDs: 0000-0002-6456-1240 (T.G.); 0000-0002-0135-7533 (C.V.); 0000-0001-7571-0670 (M.G.).Polar nuclear migration is crucial during the development of diverse eukaryotes. In plants, root hair growth requires polar nuclear migration into the outgrowing hair. However, knowledge about the dynamics and the regulatory mechanisms underlying nuclear movements in root epidermal cells remains limited. Here, we show that both auxin and Rho-of-Plant (ROP) signaling modulate polar nuclear position at the inner epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…This ability for ACT7 to show highly regulated expression is consistent with the strong upregulation of its expression during protoplast culture. A consequence of this variable expression is also that the various act7 mutants are defective in aspects of root growth and development [10,11]. Our quantitative gene expression analysis showed that ACT7 was the dominant ACT gene expressed across culture of wild-type protoplasts (Figure 4) and that the expression of ACT7 along with ACT8 partially compensated for the absence of ACT2 in the act2-1 mutant.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This ability for ACT7 to show highly regulated expression is consistent with the strong upregulation of its expression during protoplast culture. A consequence of this variable expression is also that the various act7 mutants are defective in aspects of root growth and development [10,11]. Our quantitative gene expression analysis showed that ACT7 was the dominant ACT gene expressed across culture of wild-type protoplasts (Figure 4) and that the expression of ACT7 along with ACT8 partially compensated for the absence of ACT2 in the act2-1 mutant.…”
Section: Discussionmentioning
confidence: 86%
“…ACT7 mutants also show delayed germination and altered root growth, possibly explaining the strong selective disadvantage of act7-4 when grown in competition with wild-type plants [10]. Nuclear migration and positioning to establish polar outgrowth of root hairs requires ACT7 [11], whereas ACT2 is required for bulge site selection and tip growth [12]. Furthermore, an ACT2-dependent defect in root hair growth could not be complemented by overexpression of ACT7 in the act2 mutant [13].…”
Section: Introductionmentioning
confidence: 99%
“…SnRK2.4 binds fatty acid derived lipid phosphatidic acid to associate with the plasma membrane (Julkowska et al, 2015) and responds to changes in cell osmotic status (Munnik et al, 1999), while SPK1, WDL5 and LARP1C are connected to plant hormone signaling through abscisic acid (WDL5; Yu et al, 2019), jasmonic acid (LARP1C; B. Zhang, Jia, Yang, Yan, & Han, 2012) and auxin (SPK1; Lin et al, 2012;Nakamura et al, 2018). Of these three proteins with concerted phosphorylation and abundance changes only SPK1 showed a parallel increase in abundance and phosphorylation at the same transition ( Figure 5), while WDL5 and LARP1C exhibited opposing patterns of phosphorylation and abundance changes, suggesting that phosphorylation may regulate their turnover.…”
Section: A Small Subset Of the Transition Phosphoproteome Has Proteinmentioning
confidence: 99%
“…Knowledge about how the structure of the nucleus is generated and how it responds to developmental and biotic/abiotic signals is described in the Update by Groves et al (2018). The issue also contains an article that analyzes how nuclear position is controlled during root hair differentiation (Nakamura et al, 2018).…”
Section: Cellular Responses To Stressmentioning
confidence: 99%